Pendidikan Transformatif: Elektabilitas Santri (kaum sarungan) menjadi Pemimpin Idaman - Nanang Qosim; Saifur Rohman (LP3M UNZAH GENGGONG, 2021)
Transformative education is an education that focuses on changing the behavior of students for the better. Transformative education includes social entities related to social texts in it. Transformative education at the final peak becomes a virtuous human being and is useful for others. Being a leader is not easy, being able to understand very well who he is and who he leads, a leader must know his function as a leader, understand the situation and conditions that are happening, work hard, work together, give appreciation to subordinates who have high performance, keep focus on the goal to be achieved. The electability of santri to become a leader is no longer taboo, because reality sees with the naked eye that students have significant potential. Key word: Transformative Education, Leaders and Santri